Penentuan Wilayah Lokasi Tempat Pembuangan Akhir (TPA) Sampah Kabupaten Kediri Jawa Timur - Sukartani, Ni Made; Suji, Suji (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
This study was conducted to determine the location of the final waste disposal site in Kediri Regency. The district has a very large potential for waste generation, on the other hand it only has one landfill location, while the location is close to the airport development plan, thus requiring a new location that is adequate, strategic, economical and environmentally friendly. The methodology used is a qualitative research method, using primary and secondary data, with data collection techniques through observation, interviews, literature study and documentation. Determination of the location of an adequate, strategic, economical and environmentally friendly waste landfill site is carried out through regional analysis, allowance analysis and determination. Based on this analysis, alternative locations for landfills in Kediri Regency are generated in four villages located in two sub-districts, namely Mojo Village and Sukoanyar Village in Mojo District and Selopanggung Village and Sidomulyo Village in Semen District.